Upaya Meningkatkan Partisipasi Aktif Murid melalui Metode Diskusi dan Presentasi pada Mata Pelajaran PPKn di MAS Nurul Yaqin Dawi-Dawi Kabupaten Kolaka - Dede Sopiandy; Sri Hariati; Slamet Hariyadi; Rahmi Ramadhani Abdul Asis; Suci Nurfitriani Umar (Universitas Hamzanwadi, 2026)
The low level of students’ active participation in Civic Education (PPKn) learning, which is still dominated by lecture-based methods, is the main problem addressed in this study. Previous studies generally examined discussion or presentation methods separately and focused more on cognitive learning outcomes, thus failing to comprehensively optimize students’ active participation. Therefore, the novelty of this study lies in the integration of case-based discussion methods and structured presentations within a single learning cycle in the context of Madrasah Aliyah, making the learning process more contextual and participatory. This study aims to improve students’ active participation through the implementation of discussion and presentation methods in accordance with the characteristics of Classroom Action Research (CAR), which focuses on improving the learning process rather than testing effectiveness. The study employed the Kemmis and McTaggart model conducted in three cycles, consisting of planning, action, observation, and reflection stages. The subjects of this study were 23 tenth-grade science students at MAS Nurul Yaqin Dawi-Dawi. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The results showed that students’ active participation increased significantly in each cycle. In Cycle I, participation was still low and learning was teacher-centered. In Cycle II, case-based discussions using student worksheets began to increase student engagement. In Cycle III, the integration of discussion and presentation methods was implemented effectively, with 85% of students categorized as highly active and 15% as moderately active, with no passive students. In addition, improvements were observed in students’ argumentation skills, confidence in expressing opinions, and the quality of academic interaction. These findings indicate that discussion methods contribute to the development of critical thinking, while presentation methods enhance communication skills and speaking confidence. The integration of both methods creates a more participatory, collaborative, and meaningful learning environment.